Balanced Scorecard: Performance Measurement Of University Mediated By Student Loyalty - Novi Rukhviyanti (Jurnal Manajemen, 2025)
This study aims to find empirical evidence of a Balanced Scorecard (BSC) to enhance university performance with student loyalty as a mediating variable. This research employs a quantitative method, and data is collected through questionnaires distributed to 118 students at Indonesia Mandiri University. The data was analysed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings suggest that internal business processes and financial perspectives significantly affect higher education institutional performance. While student trust, learning and growth perspective and college student loyalty have insignificant effects on institutional performance. Student loyalty mediates the relationship between student trust and financial perspective on institutional performance. Student loyalty cannot mediate the relationship between internal business processes and learning and growth on institutional performance. Future studies should investigate student expectations of learning and teaching independently, perhaps from a qualitative perspective, and explore interventions to help manage these expectations when necessary.